1988
DOI: 10.1902/jop.1988.59.12.816
|View full text |Cite
|
Sign up to set email alerts
|

CPITN Assessment of Periodontal Disease in Diabetic Patients

Abstract: The aim of this study was to investigate, using the CPITN system, the periodontal treatment needs in diabetic patients, and to shed additional light on the possible effects of the duration and control of diabetes on the periodontal status in these patients. A comparison was made between 222 diabetic patients (mean age, 46.9 years) and 189 control subjects (mean age, 43.9 years). Edentulous patients were not included in the study. The results indicated that diabetic patients demonstrated significantly more miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(28 citation statements)
references
References 11 publications
4
23
0
Order By: Relevance
“…This finding is in accordance with study by Bacic et al ,[11] who showed that periodontal disease is more frequent and severe in diabetics as compared to non-diabetics. Hayden and Bucklay[12] demonstrated that in diabetics with periodonitis, other than impaired glucose metabolism, genetic predisposition plays an important role in the progression of disease.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with study by Bacic et al ,[11] who showed that periodontal disease is more frequent and severe in diabetics as compared to non-diabetics. Hayden and Bucklay[12] demonstrated that in diabetics with periodonitis, other than impaired glucose metabolism, genetic predisposition plays an important role in the progression of disease.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the World Health Organization (WHO) statement that up to age thirty four (34), teeth are usually extracted as a result of caries but later as a result of periodontal disease as the individual grows older [18]. In addition, research on an Irish population reported that the number of missing teeth increased with increase in age of the patient and duration of diabetes mellitus [19]. That Irish study is in consonance with the result here where the 65-74years age-group who might had suffered from diabetes mellitus for a longer number of years, recorded the highest number of missing teeth with an average of 7.31 in diabetic patients.…”
Section: Discussionsupporting
confidence: 84%
“…Bacic et al . [23] also reported similar findings with a mean number of extracted teeth significantly higher among the diabetic group (12.3) than control group (9.7). In a study by Emingil et al .,[24] the mean number of missing teeth among the patients with acute myocardial infarction was 8.88 ± 7.09 and chronic coronary heart disease (CHD) was 10.3 ± 7.3.…”
Section: Discussionsupporting
confidence: 60%
“…This was similar to the study by Bacic et al . [23] (the CPITN code 4 was found in an average of 1.3 sextants in the diabetic and 0.3 sextants in the control group subjects).…”
Section: Discussionmentioning
confidence: 99%